Optimalisasi Pengawasan Barang Beredar Oleh Upt Perlindungan Konsumen Jember Untuk Meningkatkan Keamanan Konsumen Dan Kepatuhan Peraturan Bagi Pelaku Usaha - Nasrul Fuad Abdillah; Dewi Farah Adiba; Sofiah (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Supervision needs to be carried out, especially in monitoring circulating goods and business actors, where with supervision we can find out how goods are circulating on the market, whether they comply with existing regulations or not. Having supervision of business actors can minimize the occurrence of fraudulent conditions committed by business actors so that consumers feel safe and obtain their rights as consumers. This research aims to provide information and knowledge regarding the supervision of circulating goods carried out by the Jember Consumer Protection UPT in the PBBJ & TN sector, to increase consumer protection and compliance for business actors. The research method used is a qualitative descriptive method. The type of research used is direct research or field research on the object of the problem raised by the author. The results of this research indicate that the Jember Consumer Protection UPT has optimized monitoring of circulating goods on a regular basis. It can be seen from the data from monitoring goods in circulation that many business actors comply with regulations and do not sell goods that do not comply with applicable regulations.